The Severity of Fusarium Wilt Disease in Correlation to the Abundance of Fusarium oxysporum and Phytonematodes: Case Study at Banana Plantation PTPN VIII Parakansalak - Tanjung, Mei Rani; Munif, Abdul; Effendi, Yunus; Tondok, Efi Toding (Jurnal Fitopatologi Indonesia, 2022)
The Severity of Fusarium Wilt Disease in Correlation to the Abundance of Fusarium oxysporum and Phytonematodes: Case Study at Banana Plantation PTPN VIII Parakansalak Fusarium oxysporum f. sp. cubense is a soil-borne pathogen that infects banana plants and causes wilt. Several studies demonstrated that phytomatodes have a role in helping infection of the pathogens that cause wilt. This study aims to determine the relationship between phytonematodes and Fusarium oxysporum f. sp. cubense from soil and banana roots infected with fusarium wilt. Soil samples was obtained from infected banana plants and collected based on different scores of fusarium wilt disease severity. Samples were then composited based on the score, and the abundance of each pathogen is measured following samples extraction in the laboratory. The highest population of phytonematodes was 77 g-1 obtained from soil with a disease severity score of 4; and the lowest was 16 g-1 from samples with a score of 2. As for root samples, the highest population of phytonematodes (85 g-1) was obtained from plants with a score 0 and the lowest (33 g-1) was from plants with a score 3. Two species of phytonematodes were identified, i.e. Helicotylenchus sp. and Radopolus sp. Based on measurement using conventional methods showed that the abundance of Fusarium oxysporum f. sp. cubense was highest in plants with a score of 1, i.e. 8.1 × 103 cfu g-1 soil and lowest in plants with a score of 0 i.e. 1.0 × 103 cfu g-1 soil. The effect of Fusarium oxysporum f. sp. cubense to the severity of fusarium wilt shows a positive relationship of 8.3% and it may contribute to cause fusarium wilt disease by 0.6%. This pathogen can cause wilting of bananas without the help of the phytonematode species found in this study.